A textlinguistic and genological approach to the letters of application - Gillaerts, Paul (HERMES - Journal of Language and Communication in Business, 2003)
In this article we analysed a corpus of letters of application that received an evaluation by the recruiters. We investigated whether there existed a correlation between the structural and linguistic characteristics of the letters and the positive or negative evaluation by the recruiting ofﬁcers. For the rhetorical structure of the letters of application, we adopted the genre approach by Bhatia (1993); for the persuasiveness of the style we used the metadiscursivity classiﬁcation of Louhiala-Salminen (1999). Both the move structure and the metadiscursivity seem to play an important role in the appreciation of the letters of application by the recruitment ofﬁcers. There is a signiﬁ cant correlation between the evaluation by the recruitment ofﬁcers on the one hand and the rhetorical structure and the use of metadiscursive elements on the other hand.